Teaching Bukhara Children Folk Songs in Music Lessons as an Actual Problem - Khudoynazarovich, Madrimov Bahrom (International Journal of Psychosocial Rehabilitation, 2020)
The articleis devoted to teaching students how to sing in music lessons, introducing contemporary, folk songs on various genres, characters, themes, samples of composer art, brotherly and foreign music, mainly through listening to music. In this process, the student listens to music and then begins to practice, whether they are singing, playing on children's instruments, performing rhythmic and dance moves appropriate to the music, theoretical, practical knowledge, skills and, most importantly, music perceptions are developing.